Strategi Pelayanan Terhadap Kepuasan Pelanggan Coffee Gatan di Kabupaten Wakatobi Menurut Ekonomi Syariah - Wa Ode Ayu Lestari; Sitti Rahma Gurudin (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
The purpose of this study is (1) To determine the service strategy of Coffee Gatan in Wakatobi Regency (2) To determine the satisfaction of Coffee Gatan customers in Wakatobi Regency (3) To determine the service strategy for customer satisfaction of Coffee Gatan in Wakatobi Regency. This type of research is field research, with an increase in qualitative descriptive methods. The location of this research is Coffee Gatan, Wandoka Selatan Village, Wakatobi Regency with the data used being primary data and secondary data. Data collection methods are observation, interviews, and documentation. The results of this study are (1) The service strategy implemented by Coffee Gatan is effective in creating positive experiences and customer satisfaction, which are the keys to success and loyalty in the long term. (2) The level of customer satisfaction of Coffee Gatan is relatively high. This shows that the service strategy and product quality implemented have been in accordance with customer expectations, so as to create loyalty and competitiveness in Wakatobi Regency. (3) Coffee Gatan’s service strategy is in line with sharia economic values. Services that prioritize honesty, responsibility, professionalism, empathy, and consistency not only increase customer satisfaction, but also reflect a business that is blessed and has religious value. That way, Coffee Gatan is not only a place of business, but also a field of charity in the context of Islamic muamalah.